SENI KESUSASTRAAN TRADISIONAL SEBAGAI LANDASAN KONSTRUKTIF PENDIDIKAN BERBASIS KARAKTER - Suarta, I Made (Widyadari: Jurnal Pendidikan, 2018)
National education has a strong determination to build a smart and democratic Indonesian man. Intelligence is meant not merely intellectual intelligence but also emotional intelligence, ethics, and aesthetics. Creating a man with a balanced intelligence between intellectual, moral, ethics and aesthetics is required to integrate character-based education with artistic culture. Cultural arts in character education can take the form of a constructive foundation that is able to bring the learning process towards the goal, understanding, and respecting the art of culture loaded with the values ??of human life, in order to develop the character / personality of noble and ethical learners. Character education based on the art of culture can be integrated in every level of education. Material subjects related to norms or values ??need to be developed, excerpted, and integrated with the context of cultural art that becomes the identity of a society. One of the manifestations of cultural art that can be used as a medium of cultivation of student character is traditional literature. Character education based on traditional literary art really contains a lot of exemplary and wisdom of life. Traditional literature can be used as habituation media about good things so learners are cognitive about what is right and wrong, able to feel (affective) good values ??and usually do it (psychomotor).